Ensino de biologia para estudantes surdos do ensino médio: uma abordagem bílingue Libras/Português - Baia, Iara de Lima (2023)
There are several difficulties faced by teachers in finding pedagogical tools that meet the specific needs of Deaf students. However, teaching that respects the linguistic and cultural differences of this audience is important. In this sense, the present work asks the following question: how has the teaching of Biology in bilingual schools (Libras/Portuguese) been adapted to Deaf students in terms of teaching methodologies and teaching material? Thus, the study proposes, through a qualitative action research approach, to analyze teaching practices used by teachers in teaching Biology, in bilingual schools (Libras/Portuguese) for Deaf students in Fortaleza. Furthermore, the research seeks to reflect on the difficulties faced by teachers in the process of teaching Biology in bilingual schools (Libras/Portuguese), identify methodological strategies and didactic-pedagogical resources that can generate significant learning, and present a didactic sequence (DS) of Cytology, with bilingual (Libras/Portuguese)/bicultural classes based on research findings. The field of study were two Bilingual Education schools that only have Deaf students in Fortaleza. The data was based on and compared with different studies on Deaf history, teaching and didactics, as well as with investigations in the field of teaching Biology for the Deaf, in addition to Vygostky conceptions on Deaf Education. For data analysis, Bardin's content analysis method was used. Among the results found, we found difficulties in relation to teacher training, barriers in communication and language for understanding the subjects of the subject, as well as various problems linked to the student that imply understanding and learning, in addition to difficulties related to curricular didactic aspects. In relation to methodological teaching strategies and teaching resources, we realized that non-traditional visual resources, which respect the linguistic conditions of the Deaf, are elements that contribute to the students' learning. Finally, we found that the Didactic Sequence presented as an action plan was accepted by students, proving to be a useful resource and enhancing learning in the Biology discipline for Deaf Students.